Perancangan Aplikasi Penyandian Pesan Chat Client dan Server Berdasarkan Algoritma Spritz - Widodo Arif Prabowo; Mesran Mesran; Siti Nurhabibah Hutagalung (STMIK Budi Darma, 2020)
The development of the computer world in the current era, the need to secure messages / data and for security in communication is very important. The author conducted this research aims to secure chat messages from client to server and vice versa. With this cryptographic technique used to convert chat messages into the form of certain codes with the intention that chat messages cannot be seen / read by anyone except people who have the right to read the chat messages. In this study, the Client and Server Message Chat encoding application is designed which implements the workings of encryption and decryption using the Spritz Algorithm. The results of this study are chat client and server message encoding applications with the Spritz algorithm that can encode confidential chat messages. This application was created using Microsoft Visual Basic 2008